Penerapan Model Transportasi dalam Menentukan Alokasi Distribusi Arang yang Dioptimalkan di Arang Medan - M. Arij Azhari; Putri Purnama Sari; Ahmad Albar Tanjung (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Distribution is one of the most important aspects of a company because it plays a vital role in delivering products to customers. Therefore, effective distribution management can significantly influence distribution costs. Arang Medan is a company engaged in the sale of coconut shell charcoal and has three main warehouses (sources), namely Aceh, Medan, and Pekanbaru, each with a capacity of 30 tons. The company also serves three distribution destinations, namely Pekalongan, Tangerang, and Sidoarjo, each requiring 30 tons of products. This study applies the transportation method to manage and distribute goods efficiently in order to minimize transportation costs. To solve the transportation problem, the North West Corner (NWC) method and Vogel’s Approximation Method (VAM) were used as initial solution methods, while the Stepping Stone method was employed to test and determine the optimal solution. The results showed that the total distribution cost generated by the NWC method was Rp196,000,000, whereas the VAM method produced a lower cost of Rp195,000,000. Furthermore, the Stepping Stone evaluation confirmed that the allocation obtained through the VAM method represented the optimal solution. Therefore, the application of the NWC, VAM, and Stepping Stone methods can help companies achieve a more efficient distribution system and minimize transportation costs while ensuring optimal allocation of goods.